Literature Study on the Contribution of General Practitioners in Health Promotion and Prevention Efforts - Putri Raudhatul Jannah; Yuni Arta Tambun (Nusantara Sehat: Jurnal Kesehatan Indonesia, 2025)
ABSTRACT This study aims to explore and synthesize the contributions of general practitioners (GPs) in promotive and preventive healthcare, emphasizing their role in strengthening primary health systems and community well-being. Using a qualitative descriptive approach through literature study, data were collected from scientific journals, books, and official reports published between 2015 and 2025. The analysis followed an inductive process involving data identification, reduction, categorization, and interpretation to derive key themes related to preventive practices and health promotion. The findings reveal that GPs play a vital role in health education, early detection of diseases, immunization, lifestyle counseling, and chronic disease prevention. However, challenges such as limited consultation time, workload pressures, and lack of institutional incentives hinder optimal implementation. The results also highlight the importance of interprofessional collaboration, digital health integration, and patient-centered approaches in enhancing preventive efforts. Theoretically, this study reinforces behavioral and health promotion models, while practically, it offers guidance for policymakers and educators in developing systems that empower GPs to lead preventive health strategies. Overall, the research contributes to a deeper understanding of the GP’s role as a central figure in preventive medicine and underscores the need for systemic and educational reforms to optimize health promotion and disease prevention in primary care. Keywords: General practitioners, health promotion, disease prevention, primary healthcare, qualitative study.